Sistema composicional complexo visando à hierarquização de unidades sonora, sintagmas e envelopes - Onofre, Marcílio Fagner (2009)
The present research aims to insert sound objects, independent musical entities, in the context of a complex compositional system, here called Object-Timbre System. This system was divided in three different components, sonorous unit, syntagm and envelop, in which the sound object concept elapses. The sintagm and the envelope form the two levels of contextual connection. Although focusing each component as an autonomous mean, this autonomy is not an absolute one, because in order to form syntagm and envelop it is necessary the amalgamation of the sonorous units and the syntagm. Therefore the connection is an important transport of the Object-Timbre System, and will be focus from the perspective of the Gestalt psychology, specifically from the Gestalt laws. The major or minor presence of the Gestalt laws in the construction of the component forms what we call vector of contextual connection. This vector was divided in high, average and low degree. Timbre was the musical agent from which these connections have been establisched. In this way the model constructed here inserts between the atomistic thinking, as it deals with the sonorous object, and the holistic or ecological thinking, due to the necessary connections to create components in a superior hierarchic level. For such reason we used the concept of near-decomposability created by Herbert Simon in a complex systems context. Five pieces was composed for strings: Tractus Mobilis I.a/b (for solo violin), Ideoplastie II (for violin and violoncello), Vortex Diagonal (for violin, viola and violoncello), Interceptação (string quartet) and Araneae (string quintet).